A Comparative Research of Control System Design Based on H-Infinity and ALQR for the Liquid Rocket Engine of Variable Thrust. (23rd March 2023) - Chen, Fayin; Xue, Wei; Tang, Yong; Wang, Tao
Abstract : The design and analysis procedures for the thrust controller used in variable-thrust rocket engines are substantially different from those used in conventional engines due to the large-scale thrust adjustment capabilities that result in a wide range of operating situations. In this study, two control algorithms, h-infinity and adaptive linear quadratic regulator (ALQR), are constructed, examined, and contrasted utilizing the adaptive control system architecture. Both methods are capable of producing engines that respond in less than one second, have a steady-state error of less than two percent, and are robust.